DNA Marker Screening for High-Risk Non-syndromic Hearing Loss Associated to Gene Mutations - Yasin Kareem Amin (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background:Congenital hearing loss is a debilitating disease affecting 1–3 out of 1,000 live births. According to WHO’s associated figures, in both ears, 278 million people globally suffer from moderate to extreme hearing loss. Most hearing-loss individuals live in developing countries. Many deafness and hearing problems cases were documented in our region. Those cases’ exact cause is still unknown, so we performed this study and aimed to screen DNA in high-risk Non-syndromic hearing loss patients in Arbil city. Methods: This researchscreened 132 blood samples from (80 newborns and 52 individuals) at (Hiwa Institute for deaf and mutes); their ages patients from 14 to 22 years old.MTRNR1genes were performed for molecular detection of mutant genes. The mutation gene wasamplified by multiplex tetra primer PCR. Result:G- mito-1555-F1, mito-1555-R1 (O), mito-1555-F2 (I), and mito-1555-R2 (I) hearing loss mutations were not observed in 132 blood samples from both classes and genotyped in MTRNR1. For mtDNA 12S rRNA mt.1555A>G, no mutant alleles were detected in all of the tests, and no false-positives were identified.Using all primers, fifty-two samples were easily separated on 2% agarose gel; two were outer primers, and others are inner primers. Two separate bands were observed with 52 molecular samples (wild type at 254bp and control at 341bp).Of 80 samples, 28 have control bands at 341 bp. We did not find any mutation in our 80 samples. Conclusion: MTRNR1 mutation genes were not present in collected samples in deafness-related mutation. Genetic tests for the deafness gene can better diagnose infant congenital NSHL cases than conventional screening procedures.